The Effect of E-Branding and E-Loyalty on the Online Repurchase Intention of Beauty E-Commerce Sociolla.com - Dewanti, Pelangi Puspa; Rahayu, Agus; Dirgantari, Puspo Dewi (Universitas Batanghari Jambi, 2024)
This research is a quantitative research that examines social phenomena with the aims to determine the effect of E-Branding and E-Loyalty on Online Repurchase Intention of Beauty E-Commerce Sociolla.com. The population of this research is Sociolla consumers. This research took a sample of 100 respondents through a non-probability sampling technique using purposive sampling method. The data collection for this research was in the form of distributing questionnaires to consumers who had bought and used scarlett whitening products. The data analysis technique used is descriptive analysis and inferential analysis by the Partial Least Square (PLS) 4.0 analysis tool. The results of this study state that the E-Branding has a significant effect on Online Repurchase Intention and E-Loyalty has a significant effect on Online Repurchase Intention.